Relasi Penerapan Elemen Interior Healing Environment Pada Ruang Rawat Inap dalam Mereduksi Stress Psikis Pasien (Studi Kasus: RSUD. Kanjuruhan, Kabupaten Malang) - Debri Haryndia Putri; Widihardjo Widihardjo; Andriyanto Wibisono (Journal of Visual Art and Design, 2013)
The pleasing atmosphere of medical environment is a friendly atmosphere so it can accelerate the adaptation process of patients. However, the medical environment is very often identical with fear, anxiety, and uncertainty that can suppress the immune system so that patients require longer treatment time and even hasten the complications during treatment occur. This study is conducted to analyze how to optimize the application of healing environment interior elements (such: circulation, lighting, color, interior supporting elements: natural elements, the position of social interaction and television) inside the treatment room directly affect the patients psychologically. The research is at Kanjuruhan public hospital which has simple and candid interior physical condition. The results demonstrates that the elements of nature and natural lighting are potential to reduce patient stress, given the daily conditions of people who tend to be close to nature. The differences in economic background, culture, and community demographics would produce a different perception in looking at the most ideal and suitable healing elements for their treatment environment.